Manajemen Exercise Pada Pasien Penyakit Jantung Koroner: Scoping Review - Aan Nuraeni; Anita Setyawati; Ludyta Sutendi; Marisa Widiarto; Mega Herviyanti; Mentari Yesika Putri; Milda Nurul Fitriani; Mohamad Faisal Nurjaman; Moudy Muhaiminurrohima; Muhamad Makbul Mubarok; Nandi Prima Yudha; Nopa Rina Rahayu; Novianty Ayu Lestari; Nur Agustina Ningsih; Nuraiziza Fatturahmi; Rahayu Suci Lestari (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: One factor that increases physical capacity and reduces psychological problems and complications in patients with CHD is exercise. However, not all exercises are safe. Therefore, this literature study aimed to determine the types of exercise that may be performed for CHD patients. Methods: This literature review was a scoping review. The Articles were obtained from the CINAHL, ScienceDirect, and PubMed databases. The search keywords used Coronary Heart Disease OR Coronary Artery Disease OR Coronary Disease OR Ischemic Heart Disease, Exercise OR Physical Exercise OR Exercise Therapy, Recurrence OR Relapse OR Secondary Prevention. The literature was then selected based on inclusion criteria, including articles published in 2017-2021, using English, topics discussing exercise in CHD, research samples were patients diagnosed with CHD, and the full text was available. Results: From the initial search, 1275 articles were found, but after being selected, only four articles were included in the qualitative analysis. Several exercises were identified from the analysis results, including Moderate Intensity Interval Training (MIIT), Home Based Exercise, Qigong Exercise, and Continuous Moderate Intensity Exercise Training. The four exercises were practical physical exercises and can be performed by patients. Of the four exercises, the most prominent was the Home-Based Exercise because it was very efficient in terms of time and cost. Conclusion: Moderate Intensity Interval Training (MIIT), Home Based Exercise, Qigong Exercise, and Continuous Moderate Intensity Exercise Training are types of exercises that are safe to do in patients with CHD while, in practice, require monitoring.